Social Change in Rural Communities: A Pilot Study of Liberating Service-Learning with Rural Higher Education - Garret J. Zastoupil (The University of Alabama, 2022)
This exploratory study examines how service-learning faculty and community partners affiliated with rural colleges and universities engage in a practice aligned with Stoecker's (2016) proposed liberating service-learning framework. Findings from 10 in-depth interviews indicate the ongoing emphasis on student learning, increased interface with government leaders, local businesses, and advocacy organizations, and distinct contextual factors faced by service-learning partners in rural areas. These findings complicate Stoecker's initial framework, which completely decenters student learning, and calls for a deeper understanding of who constitutes community, change, and power broadly and in the context of densely connected rural areas. It also places the liberating service-learning framework within a theory of community development and outside of its ongoing emphasis as an experimental education model.